Lost in Transduction: From Law and Code’s Intra-actions to the Right to Explanation in the European Data Protection Regulations - Tedeschi Miriam; Viljanen Mika (Springer, 2025)
Recent algorithmic technologies have challenged law’s anthropocentric assumptions. In this article, we develop a set of theoretical tools drawn from new materialisms and the philosophy of information to unravel the complex intra-actions between law and computer code. Accordingly, we first propose a framework for understanding the enmeshing of law and code based on a diffractive reading of Barad’s agential realism and Simondon’s theory of information. We argue that once law and code are understood as material entities that intra-act through in-formation, the concept of transduction allows us to trace how they push each other towards change. After developing the theoretical tools, we deploy them to make sense of how law and code have changed in response to increasing automation of decision-making and the appearance of unexplainable artificial intelligence (AI) code. Thus, we employ a case study to trace transformations of the right to explanation under the European data protection regulations. This provides the backdrop for our account of how law transduces into code (and vice versa) and a proving ground for our framework.